APPLICATION OF PIEZOSURGERY IN EXTRACTION OF IMPACTED THIRD MOLARS - Gigovska Arsova, Ana; Nikolovski, Bruno; Trajculeski, Stavre; Terzievska, Aneta; Velickovski, Boris (Journal of Morphological Sciences; Vol 5 No 2 (2022): JMS, 2022)
Removal of impacted permanent third molars is considered to be one of the most common and routine oral surgical procedures. This intervention is usually performed in the classical way with the use of rotatory  instruments and burs. As an alternative to this classical approach, piezosurgery can be used, which is an osteotomy technique based on ultrasonic vibrations. The crucial advantage of piezosurgery is that it is inert to soft tissues. The aim of this study was to compare piezosurgery with the rotatory osteotomy technique, with particular reference to the time required to perform the intervention and the intensity of postoperative sequelae: pain, swelling, and trismus. This paper summarizes published experiences and knowledge of piezosurgery, with special regard to the extraction of mandibular third molars. For the purposes of this research, an automatic detailed search was performed on the electronic database PubMed for the period 2012-2022. Keywords used in the search were: piezosurgery, impacted third molars. The initial filtration resulted in 47 scientific papers, 17 of which met the selection criteria. Of particular interest were papers such as Meta-analyzes and systematic reviews. A review of the literature indicates that although patients undergoing piezosurgery required longer operating times, they had less postoperative pain, swelling, and trismus. Keywords : impacted molar, piezosurgery.